Periocular necrotizing soft tissue infection in Greater Copenhagen. Issue 2 (29th July 2019) - Würtz, Natacha Storm; Mikkelsen, Lauge Hjorth; Jørgensen, Jesper Skovlund; Hansen, Michael Stormly; Madsen, Martin Bruun; Hyldegaard, Ole; Heegaard, Steffen
Abstract: Purpose: Necrotizing soft tissue infection, also known as necrotizing fasciitis (NF), is a fast‐spreading life‐threatening infection that most commonly affects the lower limbs, groin, or abdomen. Periocular necrotizing fasciitis (PNF) is rare. Limited data exist on PNF immune cell subset; hence, this study aims to determine the representation of immune cell subsets in patients diagnosed with PNF using immunohistochemical stainings. Methods: All patients diagnosed with PNF at Copenhagen University Hospital from 2008 to 2018 were included. Their electronic medical records and pathology reports were assessed, and available tissue specimens were reviewed and stained with monoclonal antibodies for CD1a + Langerhans' cells, CD3 + T lymphocytes, CD15 + granulocytes, CD44 + lymphohematopoietic cells, CD68 + histiocytes, CD79 α + B lymphocytes, and FXIIIa+ dendritic macrophages and Langerhans' cells. The number of positive cells was counted, and an average score was calculated. The location of immune cells and bacteria was assessed. Results: The specimens were characterized by acute inflammation and necrosis of the fascia, while striated muscle involvement was less frequent. Haemolytic group A streptococci and Staphylococcus aureus were identified and mainly located in the deep dermis and subcutis in close relation to the fascia. Only few areas harboured both bacteria and inflammatory cells. Granulocytes, histiocytes and CD44 + lymphohematopoietic cells were demonstrated to be abundant in all patients, while B and T lymphocytes, dendritic macrophages and Langerhans' cells were less frequent. Conclusion: The immune cell subsets found in this study of PNF were consistent with those identified in the literature on NF in other anatomical locations. This study concludes that immune cells are abundant and exhibit a typical pattern in PNF.